Comportamento ingestivo de novilhos em função da tendência racial europeia e zebuína - Grazziotin, Milena Dutra (My University, 2022)
The racial characteristic of cattle is a determining factor in their behavior in the field. The objective was to evaluate the effect of the racial tendency and the day shift on the ingestive behavior of beef steers. The experiment was carried out in Bom Jesus/RS, at Fazenda Congonha, from May to June 2022. Ten steers with Aberdeen Angus racial tendency (maternal) crossed with Aberdeen Angus (paternal) and ten animals with Aberdeen Angus racial tendency were selected. (maternal) crossed with Tabapuã (paternal), with an average body weight of 280 to 300 kg. The evaluations took place in a paddock composed of cultivated pasture of ryegrass (Lolium multiflorum) and black oat (Avena sativa), with an approximate area of 12 hectares. The evaluations were carried out in the period between 8 am and 6 pm, with an interval of 10/10 minutes per animal, with the annotation of the behaviors performed by the in-person evaluator. The time spent grazing, rumination, leisure, walking, drinking water, defecating/urining, eating mineral salt and evaluating the frequency and time that the animals remain in the shade were evaluated. The experimental design was completely randomized, with 10 repetitions of each experimental group (Heifer: Experimental unit) and 20 evaluations of each racial pattern (two days of evaluation). The results, after converted into percentage averages, were submitted to analysis of variance and the averages were compared by Tukey's test (5%), using the Agroestat® program. Ingestive behaviors in the total day were significantly influenced (p<0.05) by the racial tendency of the animals. Grazing, ruminating and idle behaviors were significantly influenced (p<0.05) both by the evaluation shift and by the breed trend of the animals. Animals with a European racial tendency showed more time spent on grazing when compared to animals with a zebu tendency, while animals with a zebu tendency showed more time spent on rumination. The racial trend and the day shift are important factors to adjust the best management of cattle in extensive grazing. [resumo fornecido pelo autor]
A característica racial dos bovinos é um fator determinante no seu comportamento a campo. O objetivou-se avaliar o efeito da tendência racial e do turno do dia, no comportamento ingestivo de novilhos de corte. O experimento foi realizado em Bom Jesus/RS, na Fazenda Congonha, no período de maio a junho de 2022. Foram selecionados dez novilhos com tendência racial Aberdeen Angus (materno) cruzado com Aberdeen Angus (paterno) e dez animais com tendência racial Aberdeen Angus (materno) cruzado com Tabapuã (paterno), com peso corporal médio de 280 a 300 kg. As avaliações ocorreram em um potreiro composto por pastagem cultivada de azevém (Lolium multiflorum) e aveia preta (Avena sativa), com área aproximada de 12 hectares. As avaliações foram realizadas no período compreendido entre as 8h até as 18h, com intervalo de 10/10 minutos por animal, com a anotação dos comportamentos realizada pelo avaliador presencial. Foram avaliados os tempos despendidos com pastejo, ruminação, ócio, caminhada, tomar água, defecar/urinar, comer sal mineral e avaliar a frequência e o tempo que os animais permanecem na sombra. O delineamento experimental foi completamente casualizado, com 10 repetições de cada grupo experimental (Novilho: Unidade experimental) e 20 avaliações de cada padrão racial (dois dias de avaliação). Os resultados, após convertidos em médias percentuais, foram submetidos a análise da variância e as médias comparadas pelo teste de Tukey (5%), utilizando o programa Agroestat ® . Os comportamentos ingestivos no total do dia foram influenciados significativamente (p<0,05) pela tendência racial dos animais. Os comportamentos de pastejo, ruminação e ócio foram influenciados significativamente (p<0,05) tanto pelo turno de avaliação quanto pela tendência racial dos animais. Animais com tendência racial europeia apresentaram maior tempo despendido com o pastejo quando comparados aos animais com tendência zebuína, enquanto os animais com tendência zebuína apresentaram maior tempo despendido com ruminação. A tendência racial e o turno do dia são fatores importantes para ajustar o melhor manejo de bovinos em pastoreio extensivo. [resumo fornecido pelo autor]
Keywords: Agronomia; Bovino; Pastagens